The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0139774
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Characterization of Sheep (Ovis aries) Milk Whey Proteome and Comparison with Cow (Bos taurus)

Abstract: An in-depth proteomic study of sheep milk whey is reported and compared to the data available in the literature for the cow whey proteome. A combinatorial peptide ligand library kit (ProteoMiner) was used to normalize protein abundance in the sheep whey proteome followed by an in-gel digest of a 1D-PAGE display and an in-solution digestion followed by OFFGEL isoelectric focusing fractionation. The peptide fractions obtained were then analyzed by LC-MS/MS. This enabled identification of 669 proteins in sheep wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 51 publications
1
45
1
1
Order By: Relevance
“…In addition to a-lact, defense-related proteins, and IGF-II/IGF-binding proteins, more than 100 proteins were identified in the milk of the Yangtze finless porpoise (Table S1). Many of the proteins in this study were also recently reported in the milk of animals and humans (D'Alessandro et al 2010, Ogawa et al 2014, Ha et al 2015, Scumaci et al 2015, Yang et al 2015. In addition to being a source of amino acids for newborns (L€ onnerdal 2003), the physiological functions of most milk proteins remain uncertain (Table S2) and thus require in vivo experiments to verify.…”
mentioning
confidence: 70%
“…In addition to a-lact, defense-related proteins, and IGF-II/IGF-binding proteins, more than 100 proteins were identified in the milk of the Yangtze finless porpoise (Table S1). Many of the proteins in this study were also recently reported in the milk of animals and humans (D'Alessandro et al 2010, Ogawa et al 2014, Ha et al 2015, Scumaci et al 2015, Yang et al 2015. In addition to being a source of amino acids for newborns (L€ onnerdal 2003), the physiological functions of most milk proteins remain uncertain (Table S2) and thus require in vivo experiments to verify.…”
mentioning
confidence: 70%
“…Over the past 10 years the industry of production and application of biologically active additives when manufacturing functional food products has been developing intensively [13]. Creation of new food products that, in contrast to traditional food, produce a targeted effect allows preventing and correcting the consequences of human diseases [15].…”
Section: Results Of Research Into Using the Cryopowder "Amaranth" In mentioning
confidence: 99%
“…A technology was developed for producing functional concentrates from dried whey enriched with plant supplements [8,11,13].…”
Section: Results Of Research Into Using the Cryopowder "Amaranth" In mentioning
confidence: 99%
“…The SCW was generated by adding 1 mL rennet (Reno Ltd., Timaru, New Zealand) per 1 L of milk, and the cheese whey fraction was retained and frozen at −20 °C following harvesting of the cheese curd. We have previously reported on the composition of the SCW (Ha et al ., , ).…”
Section: Methodsmentioning
confidence: 99%